Madzhab Kualitas Ashahhul Asanid Prespektif Imam al-Dhahabi - fransiska, Nanda; Arianti, Vira Dindia; Muhid, Muhid; Nurita, Andris (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2023)
AbstractThis article is specifically for knowing hadith narrators in their capacity as narrators, so their study is included in the field of Rijal al-Hadith science. In further discussion, from this branch of knowledge emerged the science of al-Jarh wa al-Ta'dil and the science of Tarikh al-Ruwah. namely the sciences that discuss the credibility, personal integrity and intellectual capacity of the narrators as well as living history (biography). In collecting data, the library research method was used (library). And this research is included in descriptive qualitative research with a literature review approach. This study attempts to discuss more deeply the thoughts of Imam al-Dhahabi> on hadith critics.Keywords: Asanid Hadith; Hadith criticism; Imam al-Dhahabi.AbstrakArtikel ini khusus untuk memperoleh kajian ashahhul ashanid hadis yang membahas perawi hadis dalam kepasitasnya sebagai perawi, maka kajiannya termasuk dalam bidang ilmu Rijal al-Hadis. Dari cabang ilmu ini muncul al-Jarh wa al-Ta’dil dan ilmu Tarikh al-Ruwah yakni ilmu-ilmu yang membahas tentang kreadibilitasnya, integritas pribadi dan kapasitas intelektual para perawi serta sejarah hidup (biografi). Sehingga tujuan dari peneliti untuk menemukan kualitas ashahhul ashanid menurut prespektif imam al-Dhahabi>. Penelitian ini masuk ke dalam metode penelitian kualitatif diskriptif dengan pendekatan kajian pustaka. Dalam pengumpulan data digunakan metode library reseach (kepustakaan). Penelitian ini lebih memfokuskan mengenai pemikiran imam al-Dhahabi> pada kualitas tingkatan kesahihan perawi hadis.Kata Kunci: Asanid Hadis; Imam al-Dhahabi>; Kritik Hadis